SISTEM PELAYANAN NASABAH PRIORITY DITINJAU DARI PERSPEKTIF EKONOMI ISLAM (Studi Di Bank Syariah Mandiri Kantor Cabang Pembantu Bogor Jalan Baru) - Novi Fransiska; Rully Trihantana; Ria Kusumaningrum (Jurnal Penelitian Perbankan Syariah: Program Studi Perbankan Syariah., 2022)
This research is motivated by the existence of Bank Syariah Mandiri, apart from being a means of accommodating the interests of the Indonesian people, especially Muslims, there is also an important goal, which is to be of benefit to all levels of society. Bank Syariah Mandiri has a product, namely BSM Prioritas, where the services provided to BSM Prioritas customers get privileges from bank officers or better known as getting excellent service (service excellent). This research was conducted at Bank Syariah Mandiri KCP Bogor Jalan Baru which is located at Jl.K.H Sholeh Iskandar No.77 A Bogor (16164). This research took place from October to December 2019, the authors are interested in conducting this research to find out: how is the customer service system prioritized from an Islamic economic perspective, how are the services provided by bank officers to their customers, both Regular customers and Priority customers, and how how to view the Islamic economy on the excellent service provided by Bank officers to Priority customers. To find out the problems in this study, the authors conducted qualitative research. The data collection method used in this research is by conducting interviews, observation and documentation. This data collection method is aimed at bank officers who usually serve priority customers directly. Interviews, observations and documentation were conducted in person on 4 December 2019 at the BSM Bogor Jalan Baru office. The analysis used in this research is descriptive qualitative. The results of the study show that Prima services are intended for Priority customers, there should be no difference between regular customers and Prioritas customers. However, when viewed from the basic value of Islamic Priority Banking services, there is no problem as long as it does not harm other parties and does not deviate from the provisions set by Allah SWT.